Influence of winter Saharan dust on equatorial Atlantic variability - Ignasi Vallès-Casanova; Ori Adam; Marta Martín Rey (Communications Earth & Environment)
Abstract While Saharan dust’s influence on sea surface temperature variability in the tropical North Atlantic is well-documented, its effects on the equatorial region remain underexplored. This relationship is particularly important due to the strong influence of equatorial Atlantic variability on both local and remote climates. Here, we use observational and reanalysis data to investigate Saharan dust’s role in boreal winter, a period when dust transport is typically near the equator. A unique footprint of Saharan dust forcing is revealed, as well as a complex, non-monotonic response. Specifically, in contrast to the expected cooling due to shortwave blocking by Saharan dust, lower tropospheric warming, and stabilization lead to a strong sea surface warming off the coast of northwestern Africa and to the development of an off-equatorial warm front. The front drives cross-equatorial winds that induce a northward shift of the Atlantic rain belt, equatorial cooling, and equatorial wave activity leading to delayed equatorial warming. Winter Saharan dust is therefore an important contributor to equatorial Atlantic variability, with cross-regional implications.